Bureaucratic Leadership Head of the Office of Population and Civil Registry Office of Soppeng - Harbani Pasolong; Tunggul Prasodjo (Program Pascasarjana Universitas Negeri Makassar, 2022)
The purpose of this study is to find out how maximal the bureaucratic leadership is carried out by the Head of the Soppeng Regency Population and Civil Registry Office. This research uses descriptive research type. The sampling technique used is saturated sampling technique, while the data collection methods used are observation and questionnaires. The data obtained using quantitative analysis and presented in the form of a frequency distribution table, where the scale used is the Likert scale. The results showed that the implementation of bureaucratic leadership at the Population and Civil Registry Office of Soppeng Regency could be categorized as